Analisis Perbandingan Penerapan Stateless Dan Stateful Pada Aplikasi Server Load Balancing Berbasis Software-Defined Networking - Fahmi Alfareza; Achmad Basuki; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Software-defined networking or commonly called SDN is a computer network architecture in which data flow and communication control are separate. This separation makes SDN able to configure network applications more efficiently than traditional networks, one example is the server load balancing application. Server load balancing is a technique for balancing load distribution to several servers that provide a service. There are two techniques that can be implemented as server load balancing, that is stateless and stateful. The problem is, if the state on SDN affects performance on SDN-based network applications. Then, which technique has better performance to be implemented as SDN-based server load balancing seen on the client side, SDN controller, and server. On the client side, it is found that the performance of stateless is better than stateful with the throughput value of stateless 222.9% greater at request rates of 250 requests/second than stateful. On the SDN controller side, it was found that the performance of the stateless is better than the stateful with the connection rate value of the stateless 222.9% greater at the request rate of 250 requests/second than the stateful. And on the server side, it was found that the performance of stateful was better than with a more even distribution of requests. In a stateful, server 0 receives 6,667 requests, server 1 receives 6,666 requests, and server 2 receives 6,666 requests. Whereas on stateless, server 0 receives 10,000 requests, server 1 receives 5,000 requests, and server 2 receives 5,000 requests.